STUDI EKSPERIMENTAL TEKUK LOKAL BATANG BAJA RINGAN CANAI DINGIN - Astrida Puspita Sari; Agus P Rahamadi; Stefanus Adi Kristiawan (Prodi Teknik Sipil FT Universitas Sebelas Maret, 2019)
Cold-formed steel structure is the most chosen alternative in the world of building construction nowadays, because of its light weight, fast and easy to construct. This study conducted local buckling study on cold-formed steel channel section to study the critical load of cold-formed steel column when the load centric and eccentric and to indentify the failure mode through numerical and experimental study. The local buckling of cold-formed steel channel section was analyzed analytically using SNI 7971: 2013, numerically using Abaqus and Experimental at centric (COG) and eccentric (ECC) loading. The centric load calculated analytically with the formula SNI 7971: 2013 is 12.37% otherwise eccentic load 31.52% greater than the numerical analysis of the Finite Element Method (FEM) which is verified by the Experimental test. In the case of the channel section eccentric loading, the load carrying capacity decreased by 21% compared to centric loading.